Pengaruh Model Problem Based Learning (PBL) Barbasis Word Wall terhadap Peningkatan Hasil Belajar pada Mata pelajaran PKN Kelas VI SD Negeri 24 Banda Aceh - Reza Karunia; Helminsyah; Raziska Ibrahimi (Jurnal Ragam Pengabdian, 2026)
The low learning outcomes of students in citizenship education subjects in class VI of SD Negeri 24 Banda Aceh are influenced by less varied learning and the use of interesting learning media. Therefore, implementing a word wall-based problem based learning (PBL) model is an alternative for improving student learning outcomes. This research aims to determine the influence of the word wall-based problem based learning (PBL) model on student learning outcomes in class VI citizenship education subjects. This research uses a quantitative approach with a one group pretest-posttest experimental method without a control group. This research was carried out in November with a research sample of 25 people taken using total sampling techniques. The intervention took the form of implementing a word wall-based problem based learning (PBL) model which was carried out during one meeting for 70 minutes. Data was collected by pretest and posttest which was analyzed using the paired sample t-test. The research results showed that the average pretest score of students was lower than the average posttest score with a value of p = 0.000 (p < 0.05). This shows that there is a significant influence of implementing the word wall-based problem based learning (PBL) model on improving student learning outcomes. The conclusion from the results of this research shows that the application of the word wall-based problem based learning (PBL) model is a simple but effective learning approach in increasing student involvement and has a positive impact on learning outcomes in citizenship education subjects. in class VI of SD Negeri 24 Banda Aceh